2018
DOI: 10.1007/978-3-319-96071-5_33
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ‘Contributing Factors in Construction Accidents’ (ConCA) Model

Abstract: In 2005 the 'Contributing factors in Construction Accidents' framework (ConCA) introduced a sociotechnical systems approach to risk management in construction. ConCA demonstrated the value of exploring distal factors and identifying underlying or latent causes: It promoted an understanding of construction accidents as systemic accidents and challenged an industry-wide culture of blaming frontline workers. A decade later the original article has been cited by research from 37 countries, shaping inquiries and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Finally, he also analyzed the differences between these influencing factors and those in traditional cast-in-place buildings [10]. Many other scholars [11][12][13][14][15] conducted behavioral perception studies to analyze risk factors from management perspectives. Suraji (2001) [16] considered both the short-range and long-range effects during construction and found that different risk factors can interact.…”
Section: Literature Review 21 Risk Identification Of Safety Accidents...mentioning
confidence: 99%
“…Finally, he also analyzed the differences between these influencing factors and those in traditional cast-in-place buildings [10]. Many other scholars [11][12][13][14][15] conducted behavioral perception studies to analyze risk factors from management perspectives. Suraji (2001) [16] considered both the short-range and long-range effects during construction and found that different risk factors can interact.…”
Section: Literature Review 21 Risk Identification Of Safety Accidents...mentioning
confidence: 99%
“…Shin (2015) [13] studied causes of tower crane disassembly and assembly accidents from 2001 to 2011 [14] and explained safety management according to risks in workers' occupational norms, mechanical performance and quality. Some [15][16][17][18][19] explored behavioral perception and explained risk factors from the perspective of management. There are also many scholars who believe risk source events cause accidents, and achieve great results in identifying key risk factors and establishing evaluation indicators via cloud model [20,21], grey clustering [22] and other methods, providing a basic framework for understanding occurrence of safety accidents in prefabricated construction projects.…”
Section: Literature Review Risk Probability Research Of Prefabricated...mentioning
confidence: 99%
“…The following terms are how scientific papers referred to the idea of PtD: • Prevention through Design (PtD) (Ferrante, 2010;Hallowell et al, 2016;Karakhan & Gambatese, 2017;Kasirossafar & Shahbodaghlou, 2013b;Toole & Carpenter, 2013); • Design for Safety (DfS) Lee et al, 2020;Mering et al, 2017); • Safety in Design (Horberry, 2014;Li et al, 2020;Taiebat et al, 2012); • Design for Occupational Safety and Health (DfOSH) (Manu et al, 2019;Poghosyan et al, 2020); • Design Risk Management (Harvey et al, 2019;Mesaros et al, 2019).…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%